2006
DOI: 10.1074/jbc.m601320200
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-induced NADPH Oxidase Activation Impairs Insulin Signaling in Skeletal Muscle Cells

Abstract: The renin-angiotensin system (RAS) and reactive oxygen species (ROS) have been implicated in the development of insulin resistance and its related complications. There is also evidence that angiotensin II (Ang II)-induced generation of ROS contributes to the development of insulin resistance in skeletal muscle, although the precise mechanisms remain unknown. In the present study, we found that Ang II markedly enhanced NADPH oxidase activity and consequent ROS generation in L6 myotubes. These effects were block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
226
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(245 citation statements)
references
References 60 publications
13
226
0
6
Order By: Relevance
“…ROS production has been reported to be associated with reduced nitric oxide (NO) bioavailability through scavenging by superoxide anions (Wei et al 2006) and/or endothelial NO synthase uncoupling (Crabtree et al 2009). In the present study, we evaluated the instant mitochondrial ROS impregnation at two moments of the perfusion: just before ischemia and at the end of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…ROS production has been reported to be associated with reduced nitric oxide (NO) bioavailability through scavenging by superoxide anions (Wei et al 2006) and/or endothelial NO synthase uncoupling (Crabtree et al 2009). In the present study, we evaluated the instant mitochondrial ROS impregnation at two moments of the perfusion: just before ischemia and at the end of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the total volumes of non-myocyte components are small in the soleus, and earlier studies using immunohistochemistry have shown that protein levels of MCP-1 and TNF-a were increased by 1.5-fold in myocytes. 33 Therefore, we speculate that the induction of the inflammatory cytokines in response to the Ang II infusion occurred mainly in myocytes.…”
Section: Discussionmentioning
confidence: 89%
“…Aliskiren blocks the activation of RAS at the initial step of renin inhibition, and has been shown to improve glucose transport in the skeletal muscle tissue from renin transgenic rats (Lastra et al, 2009). Since Ang II is known to directly impair insulin signaling through NAD(P)H oxidase activation in skeletal muscle cells (Wei et al, 2006), aliskiren is considered to be an attractive therapeutic approach to ameliorate insulin resistance associated with HF. On the other hand, NEFA was increased in MI mice and was normalized by aliskiren, suggesting that HF-induced lipolysis of adipose tissue is alleviated by aliskiren.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the peripheral effects of insulin resistance are likely to represent a major metabolic feature of the pathophysiology of HF, contributing to key clinical symptoms such as breathlessness and early muscle fatigue (Kinugawa et al, 2015;Okita et al, 2013;Wilson et al, 1993). Multiple mechanisms of insulin resistance have already been identified, including increased oxidative stress and hyperactivation of the renin-angiotensin system (RAS) (Officers et al, 2002;Wei et al, 2006). We previously reported that insulin resistance was induced in experimental HF in mice (Ohta et al, 2011), and a later study showed that this induction was accompanied by increased local angiotensin II (Ang II) in the skeletal muscle and subsequent NAD(P)H oxidase-derived oxidative stress (Fukushima et al, 2014).…”
Section: Introductionmentioning
confidence: 99%